Irradiation-induced bone sarcoma in a patient treated for cervix cancer 28 years earlier - Klimek, Małgorzata; Wilk, Wacław; Szostek, Sława; Łuczyńska, Elżbieta; Bieda, Tomasz; Kojs, Zbigniew; Ryś, Janusz (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study: To present a case of a patient with cervical carcinoma in stage IIA who was diagnosed with pelvic bone sarcoma 28 years after radiotherapy. Case presentation : A 37-year-old woman with IIA cervix cancer was treated with external beam irradiation and brachytherapy. The patient had undergone conventionally fractionated external beam irradiation using the “box” technique, with the total dose of 50 Gy and brachytherapy with radium applicators (intrauterine tube and fornix applicator) with the dose of 60 Gy calculated at point A. After treatment she was followed up for 2 years. Twenty-six years later, inoperable pelvic bone sarcoma was diagnosed within the irradiated field. The clinical course was aggressive and rapid progression during chemotherapy was observed. Conclusions : For patients receiving radiotherapy, long-term careful follow-up is mandatory due to second cancer risk. In the case of any suspicious symptoms, such patients need proper diagnosis to detect any disease as early as possible.